Lithuanian teachers – perticipants of revolutionary movement and fighters for Soviet power - Buckus, P. (Psichologija, 1974)
The life, work and social activities of Lithuanian teachers, participants of revolutionary movement and fighters for Soviet power, is a heroic page in the history of Lithuanian culture and revolution. In difficult underground circumstances of tsarist Russia and burgeois Lithuania, a great number of Lithuanian teachers joined the revolutionary movement and became active fighters for Soviet power. They have earned nationwide respect and their deeds deserve a more thorough study. The article enumerates teachers who have made the most important contribution to the final victory of proletarian revolution in Lithuania, in the fight against fascism and bourgeois nationalism, in the building of socialism in our republic.